2010
DOI: 10.1021/jp101039s
|View full text |Cite
|
Sign up to set email alerts
|

Stable p-Type Doping of ZnO Film in Aqueous Solution at Low Temperatures

Abstract: Zinc oxide (ZnO) is a wide band-gap material with excellent optical properties for optoelectronics applications. However, device fabrication has been hampered by difficulties in obtaining a stable p-type doping. Here, we present the first report on the growth and doping of ZnO film through the incorporation of potassium (K) from group I in aqueous solution at 90 °C to yield a stable p-type doping. The contribution of potassium toward p-type conductivity is confirmed using Hall effect measurements and SIMS. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Th e naturally passivating oxide on zinc, under near-neutral saline aqueous conditions (solution or drops), develops a bilayer with a thick, porous outer layer of variable composition covering a thinner, compact fi lm of ZnO at the metal interface [20]. Under atmospheric conditions, the porosity of the outer layer, comprised of corrosion products such as gordaite and zinc hydroxyl-carbonate [21], gradually decreases, providing a pH-buff ering eff ect and developing an outer oxide that possesses a negative surface charge in mildly acidic environments [22]. Th e porosity of the inner layer also decreases over time [20].…”
Section: Green Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e naturally passivating oxide on zinc, under near-neutral saline aqueous conditions (solution or drops), develops a bilayer with a thick, porous outer layer of variable composition covering a thinner, compact fi lm of ZnO at the metal interface [20]. Under atmospheric conditions, the porosity of the outer layer, comprised of corrosion products such as gordaite and zinc hydroxyl-carbonate [21], gradually decreases, providing a pH-buff ering eff ect and developing an outer oxide that possesses a negative surface charge in mildly acidic environments [22]. Th e porosity of the inner layer also decreases over time [20].…”
Section: Green Alternativesmentioning
confidence: 99%
“…For instance, ZnO is an n-type semiconductor, and cathodic reactions (i.e. oxygen reduction) can occur on the oxide pore surfaces rather than penetrating to the metal/oxide interface [22]. Modeling indicates that with zinc overlaid by such a porous oxide, the corrosion current is initially very high (due to the large cathodic area) but rapidly falls as oxygen is consumed within the pores of the oxide.…”
Section: Green Alternativesmentioning
confidence: 99%
“…Especially, the attractiveness of NiO material lies in the fact that the NiO films has an natural p-type conductivity and low preparation costs compared to the high-quality p-type ZnO and GaN materials, which are difficult to achieve due to the less stability and high resistance [5][6][7][8][9][10] . Recently, Patel et al 11 fabricated NiO/ ZnO heterojunction on plastic substrate for ultraviolet photodetector applications.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, the electrically pumped ultraviolet random laser actions have been realized by using highly disordered ZnO film and various ZnO micro-and nanostructures [4][5][6][7][8]. But it is not propitious to obtain high ultraviolet random laser performance based on ZnO random cavities due to the difficulties in producing highly conductive and stable p-type ZnO material [9][10][11][12]. Recent research has suggested that the ultraviolet random laser action could also be observed in the GaN material [13].…”
Section: Introductionmentioning
confidence: 99%